Zooplankton Abundance with NPK Fertilization - Muta Ali Khalifa; Hanna Silvia; Ujang Dindin (JURNAL PERIKANAN DAN KELAUTAN, 2017)
Zooplankton has advantages as natural feed for fish larvae. Therefore, necessary to attempts natural growth of zooplankton in aquaculture media, e.g. fertilization. This research aim to describe NPK Ferlitilizer influence to zooplankton abundance. Research conducted at January 2016, in Aquatic Resources Management Laboratory- Muhammadiyah University of Sukabumi and Water Quality Analysis in Center for Freshwater Aquaculture Laboratory. Research design is experimental research with four treatments and three replications. Treatment A with enhanced NPK fertilizer 10 ppm, Treatment B with NPK fertilizer 20 ppm, Treatment C with NPK fertilizer 30 ppm, Treatment D was control without fertilizer. Fertilizer treatment lead to water colour became green until dark green, officially different with control treatment. Zooplankton composition founded 78% from Eurotatoria, 19% from Branchiopoda, the left was from Malacostraca and Hexanauplia. Zooplankton abundance of control treatment significantly different with fertilizer treatment. The highest abundance found at the tenth day from treatment C with 18640 cell/L or almost 480% from initial.